Preparation and Application of Titanate Nanotubes on Dye Degradation from Aqueous Media by UV Irradiation - Rui Liu; Wein-Duo Yang; Hui-Ju Chueng; Bin-Qiao Ren (Journal of Spectroscopy)
Titanate nanotubes were synthesized by a hydrothermal method using commercial TiO2 powder and then used as a photocatalyst. The titanate nanotubes were synthesized by varying the hydrothermal temperature from 110°C to 180°C. The morphological changes and phase transformation of the TiO2 nanotubes were analyzed by X-ray diffraction (XRD), scanning electron microscopy (SEM), and transmission electron microscopy (TEM). The particles’ scattering behavior was investigated by Raman studies, and the surface area of the nanotubes was determined by a Brunauer, Emmett, and Teller (BET) analysis. Comparative studies show that the surface area of nanotubes increases with increasing temperature up to 130°C. The catalytic behavior of the synthesized nanotubes was also studied. The as-prepared titanate nanotubes were applied to methylene blue (MB, an organic dye) degradation in aqueous media by UV irradiation. Approximately 99% of the dye was removed from the aqueous media using 2 g/L titanate nanotube when the initial dye concentration was 9 mg/L. The total irradiation time was 2 h.